POLITIK HUKUM DALAM PENERAPAN SISTEM PERADILAN PIDANA ANAK DI INDONESIA - Vivi Arfiani Siregar; Indra Mukhlis Adnan; Muannif Ridwan (Jurnal Inovasi Penelitian, 2021)
Legal politics is a legal policy or official line (policy) on law that will be enforced either by making new laws or by replacing old laws, in order to achieve state goals. In the Indonesian constitution, the state guarantees the right of every child to survival, growth, and development as well as protection from violence and discrimination. Formulation of legal politics issues in the application of sanctions that are part of the juvenile criminal justice system, so as to change the paradigm in handling children in conflict with the law. this research is a normative legal law research or by means of the data obtained is analyzed by comparing the provisions that are normative (das sollen) with the reality (das sein) that occurs in society. The nature of the research is descriptive analytical. Conclusions can be drawn deductively, namely from general to specific. The ideal legal politics in regulating diversion to realize restorative justice in the Juvenile Criminal Justice System taken by the Supreme Court of the Republic of Indonesia is to amend Supreme Court Regulation Number 4 of 2014 concerning guidelines for implementing diversion in the juvenile criminal justice system, by adding the provisions governing, Special Judge dealing with diversion in the juvenile justice system. With this legal politics, it is hoped that a sense of justice in the diversion of the juvenile justice system will be realized.